Pertahanan Negara, Realitas Sosial Keagamaan, dan Ancaman Non-Militer Di Yogyakarta - Santosa, Edy; Soehadha, Moh; Supriyanto, Heri (Prodi Sosiologi Agama, 2021)
The concept and strategy of national security of Indonesia includes the resilience of all areas of the country against military and non-military threats. From a sociological perspective, non-military threats exist in a dynamic social and environmental world and are constantly changing in form. Non-military threats have a broader dimension, including ideological, social, economic, cultural, political, information technology and public safety. Various facts about regional conditions and socio-religious dynamics in the Special Region of Yogyakarta are indicators that show a source of problems as a potential non-military threat. The article from the field research using the following qualitative method contains an interpretive description of various non-military threats from internal conditions, as well as external influences. Internal conditions are caused by the Yogyakarta region which is directly adjacent to the Indian Ocean, the ring of fire area, and the city of study and tourism destinations. As for the external conditions for non-military threats, among others, due to the influence of globalization, geopololitical conditions, ideological flows such as radicalism and massive caiptalization from outside Indonesia. There are three forms of non-military threats in Yogyakarta that urgently need a strategy to respond and resolve them. The three non-military therats are religious radicalism, narcotics and illegal drugs, as well as the negative impact of virtual culture; such as the rise of hate and hoaxes that can damage unity, because it causes discord of the nation.